High-Pressure Studies of Crystalline Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
[This book is a printed edition of the Special Issue of Crystals: High-Pressure Studies of Crystalline Materials. It also includes additional articles published in Crystals and related to the topic of the Special Issue, which have been selected based upon their relevance and scientific quality.]